Enterotoxigenic Bacillus cereus from cooked chicken meat: A potential public health hazard - Erkihun Aklilu; Erniza Tukimin; Nur Hardy Abu Daud; Than Kyaw
This study was conducted to isolate Bacillus cereus from raw and cooked chicken meat from selected retail shops and wet markets in Kota Bharu and to determine the antimicrobial resistance patterns of B. cereus. Methodology and results: A total of sixty samples (30 from raw and 30 from cooked chicken meat) were tested for presence of B. cereus. Isolation and identification of B. cereus was done by using routine bacterial culture and Polymerase Chain Reaction (PCR). Bacillus cereus was detected in 16.67% (10/60) of the samples tested. All isolates were negative for the enterotoxigenic gene, nhe genes, however, six of the isolates were found to be positive for hbla genes. B. cereus isolates showed 100% resistance towards beta lactam antibiotics. Conclusion, significance and impact study: Although only 60 samples are analysed in the current study, the fact that toxigenic strains of B. cereus were isolated in cooked chicken meat intended for human consumption implies the potential public health risk it might pose. Further study with increased sample size, screening other toxigenic strains of B. cereus and molecular typing is recommended to have a more detailed understanding of the occurrence of the bacteria in chicken meat in Kota Bharu. It is necessary to educate the public on the risks of food contamination by bacteria that may cause food borne illnesses. Some precautions such as routine checking of the freshness of food before consumption, hygienic preparation and proper cooking of food can be implemented to reduce the risks of food borne illnesses related B. cereus and other potentially dangerous bacteria.